2014
DOI: 10.1016/j.compstruct.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of block copolymer nano-reinforcements on the low velocity impact response of sandwich structures

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. a b s t r a c tSandwich composites with fibre reinforced plastic (FRP) facesheets have emerged as a major class of lightweight structural materials in a wide range of engineering fields including aerospace, automotive and marine structures. This is due to attractive mechanical properties such as high specific stiffness and high strength. However, sandwich stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
(39 reference statements)
3
30
1
Order By: Relevance
“…Denneulin et al [73] reported significantly increased impact strength and reduced damage area for a concentration of 10 wt.% of Nanostrength®. Ramakrishnan et al [74] achieved similar results with sandwich structures, due to the nano-cavitation and the shear yielding caused by the presence of the nano-particles.…”
Section: Rubber and Thermoplastic Blendssupporting
confidence: 77%
“…Denneulin et al [73] reported significantly increased impact strength and reduced damage area for a concentration of 10 wt.% of Nanostrength®. Ramakrishnan et al [74] achieved similar results with sandwich structures, due to the nano-cavitation and the shear yielding caused by the presence of the nano-particles.…”
Section: Rubber and Thermoplastic Blendssupporting
confidence: 77%
“…Four bolts were tightened to a torque of 5 N•m in order to provide a consistent clamping condition from test to test. Similar circular fixtures were used to evaluate the low velocity impact response of sandwich panels [2,31] and composite laminates [32,33] under drop weight impact tests. A protective cage, as shown in Fig.…”
Section: Impact Testingmentioning
confidence: 99%
“…Sandwich structures are lightweight composite materials that have been widely used in numerous application fields such as aerospace, marine, automotive, and energy industries for their desirable properties like high specific bending stiffness, excellent thermal insulation, acoustic damping, etc. However, sandwich composite structures are susceptible to impact loading and may be subjected to different impacts such as tool drops, bird strikes, hail stones, and runway debris during the service life [2]. These impacts may cause significant damage, such as local core crushing and debonding of the facesheet from the core, which severely compromises the structural integrity of the sandwich panel [3].…”
Section: Introductionmentioning
confidence: 99%
“…The random copolymer containing DMA provides a better miscibility of the shell with several epoxy formulations . Addition of small amounts of these block copolymers produces a significant increase of the fracture resistance of neat epoxy formulations and their composites .…”
Section: Introductionmentioning
confidence: 99%